2020
DOI: 10.1111/cyt.12795
|View full text |Cite
|
Sign up to set email alerts
|

Adequate tumour cellularity is essential for accurate PD‐L1 immunohistochemistry assessment on cytology cell‐block specimens

Abstract: Objectives PD‐L1 immunohistochemistry (IHC) is an essential predictive biomarker for patients with non‐small cell lung cancer (NSCLC), required to inform treatment decisions regarding anti‐PD‐1 immune checkpoint inhibitor therapy. This study aims to investigate the concordance between PD‐L1 IHC assessed on NSCLC cytology and histology specimens and to determine the impactce of tumour cellularity. Methods Matched cytology and histology NSCLC specimens were retrieved from the archives of the Royal Melbourne Hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…However, the range of concordance was quite broad, 62–100% at cutoff 1% and 67–100% at cutoff 50% based on 25 publications. Also, several studies present a positive PD-L1 expression (≥1%) in <40% of NSCLC cases when using cytology [41, 42, 44, 52, 54, 61, 68, 69], which is notably lower than what has been reported in both early treatment studies and large studies with real-life data, with PD-L1 ≥1% in 53–86% [70] and 56–63% [71, 72] of NSCLC, respectively (61% for cytology [71]). Furthermore, for example, the large study by Kuempers et al [52] showed a high concordance (93%) at the 50% cutoff for a positive staining, but still no case with >50% in both cytology (mainly imprints from resections) and the paired resected tumors, which makes the applicability of the results questionable.…”
Section: Discussionmentioning
confidence: 99%
“…However, the range of concordance was quite broad, 62–100% at cutoff 1% and 67–100% at cutoff 50% based on 25 publications. Also, several studies present a positive PD-L1 expression (≥1%) in <40% of NSCLC cases when using cytology [41, 42, 44, 52, 54, 61, 68, 69], which is notably lower than what has been reported in both early treatment studies and large studies with real-life data, with PD-L1 ≥1% in 53–86% [70] and 56–63% [71, 72] of NSCLC, respectively (61% for cytology [71]). Furthermore, for example, the large study by Kuempers et al [52] showed a high concordance (93%) at the 50% cutoff for a positive staining, but still no case with >50% in both cytology (mainly imprints from resections) and the paired resected tumors, which makes the applicability of the results questionable.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies, however, have shown that the expression of different proteins evaluated by IHC corresponds between surgical resection specimens and NAB samples. [16][17][18] Given that relatively few cases had both NAB and resected PDACs, however, we were not able to statistically address the minimal threshold NAB tumor cellularity. Thus, our threshold of at least 100 viable cells in the sample to be included in the study was empirically determined but has not yet been rigorously defined.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, the adequacy criteria state that a sample must contain a minimum of 100 viable tumour cells to be eligible for quantification of PD‐ L1 expression. It is worth noting that the literature has shown that the adequacy rate of cytological samples is generally higher than 80% 21 , 42 and only occasionally lower than 70% 44 (Table 2 ). These data are remarkable if one considers the great difficulty of obtaining a sufficient number of tumour cells in small biopsies.…”
Section: Cyto‐histological Correlationmentioning
confidence: 95%